Clinical and economic impact of cost-intensive vs non-cost-intensive antihypertensive therapies: a retrospective study using real-world data from Japan - Ataru Igarashi; Hiroshi Yoshihara; Naoki Maeda; Tohru Tonoike; Hiromitsu Ohno; Susumu Nishiuchi (BMJ Open, 2025)
Background Hypertension is a major health challenge imposing substantial economic and health burdens worldwide. This study compared treatment outcomes and costs between cost-intensive and non-cost-intensive pharmacotherapies, defined by prescribing intervals and the type of drugs, using electronic health record (EHR) data from multiple healthcare facilities, focusing on the type of antihypertensive drug and prescribing patterns.Design A retrospective cohort study. A mixed-effects Cox proportional hazards model was used to investigate the association between cardiovascular events and healthcare resource use.Setting EHRs from 34 primary care facilities in Japan.Participants Patients prescribed either angiotensin receptor blockers (ARBs) alone or calcium channel blockers (CCBs) alone were included.Results During 6629 person-years of follow-up, 71 events were observed. Model diagnostics confirmed the proportional hazards assumption and substantial inter-clinic heterogeneity. The type of drug (ARBs or CCBs) had no statistically significant impact on the incidence of cardiovascular events (HR 0.999, 95% CI 0.603 to 1.655). Similarly, shorter prescribing intervals (less than 36 days) were not significantly associated with the outcome (HR 1.724, 95% CI 0.906 to 3.279). The mean annual medical cost per patient for the cost-intensive (ARB with short prescribing intervals) and non-cost-intensive (CCB with long prescribing intervals) groups was Japanese yen (JPY) 137 023 and JPY 85 911, respectively. Sensitivity analysis using different time windows yielded similar results, confirming the robustness of the findings.Conclusion No apparent reduction in cardiovascular events associated with the use of ARBs or shorter prescribing intervals was observed despite the elevated cost caused by intensive pharmacotherapy and frequent clinic visits.